A new photoelectric ink based on nanocellulose/CdS quantum dots for screen-printing. (5th September 2016) - Tang, Aimin; Liu, Yuan; Wang, Qinwen; Chen, Ruisong; Liu, Wangyu; Fang, Zhiqiang; Wang, Lishi
Highlights: Nanocellulose/CdS quantum dot composites were synthesized by an in-situ composite. The composite had a photocurrent as high as 2 μA. An novel photoelectric ink was fabricated based on the composite. The surface tension and viscosity of the photoelectric ink were investigated. The photoelectrical properties of the ink are applicable to PEs and 3D printing. Abstract: CdS quantum dots with excellent photoelectrical properties embedded in nanocellulose could be exploited for use in photoelectrical ink. In this work, nanocellulose/CdS quantum dot composites were fabricated by controlling the carboxylate content of the nanocellulose and the molar ratio of Cd 2+ /–COOH. New photoelectric inks were prepared based on the composites, in which the CdS quantum dots acted as the pigment and the nanocellulose as the binder. The results of the photocurrent of the composites showed that the photocurrent could be tailored by the carboxylate content and the molar ratio of Cd 2+ /–COOH. And the photocurrent could be as high as 2 μA. The surface tension of the photoelectric ink was 27.80 ± 0.03 mN/m and its viscosity was 30.3 mPa s. The photoelectric ink was stable with excellent fluidity and rheology, it could therefore be applied to screen-printing and three-dimensional (3D) printing.